2021
DOI: 10.2166/wst.2021.353
|View full text |Cite
|
Sign up to set email alerts
|

Urban stormwater nutrient and metal removal in small-scale green infrastructure: exploring engineered plant biofilter media optimisation

Abstract: The present study evaluated engineered media for plant biofilter optimisation in an unvegetated column experiment to assess the performance of loamy sand, perlite, vermiculite, zeolite and attapulgite media under stormwater conditions enriched with varying nutrients and metals reflecting urban pollutant loads. Sixty columns, 30 unvegetated and 30 Juncus effusus vegetated, were used to test: pollutant removal, infiltration rate, particulate discharge, effluent clarity and plant functional response, over six sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Targeted design strategies may be capable of increasing synergistic relationships among soil and vegetation structures to create co-benefits. For example increasing vegetation in LID can increase infiltration [68,69], biodiversity [70], and shading, while decreasing nutrient export [71][72][73] and urban heat islands [74].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted design strategies may be capable of increasing synergistic relationships among soil and vegetation structures to create co-benefits. For example increasing vegetation in LID can increase infiltration [68,69], biodiversity [70], and shading, while decreasing nutrient export [71][72][73] and urban heat islands [74].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic bacteria within biofilter media necessitate nutrients like nitrogen, phosphorus, potassium, sulfur, and minor components, such as additional oxygen and carbon for their development. However, the biofilter media have remaining nutrients; other nutrients are required for the long-term performance of biofilters . Subsequently, nitrogen is the second most significant component in the biomass after carbon; expanding nitrogen to the biofilter media may significantly broaden the biofilter’s performance.…”
Section: Important Factors Of Biofilters That Affect the Performance ...mentioning
confidence: 99%
“…However, the biofilter media have remaining nutrients; other nutrients are required for the long-term performance of biofilters. 121 Subsequently, nitrogen is the second most significant component in the biomass after carbon; expanding nitrogen to the biofilter media may significantly broaden the biofilter's performance. An investigation of a biofilter processing toluene showed that its performance powerfully depends upon the nitrogen source, and they proposed a stoichiometric mass proportion of 3.8, accepting that microorganisms controlled 13% of their mass as nitrogen and 50% as carbon.…”
Section: Nutrient Necessitymentioning
confidence: 99%
“…Consequently, most efforts to ameliorate the microbe removal consistency of these systems have focused on design optimisation. While biofilters have been extensively optimised for ecological pollutant removal [13,14], research into their design for enhancing faecal microbe treatment remains comparatively scarce. Limited existing research has focussed on the design and incorporation of a submerged/saturated zone (SZ) [9,15] and filter media (retention-promoting/antimicrobial) for enhanced faecal microbe removal [1,8,11,16,17], with significant advancements having been made.…”
Section: Introductionmentioning
confidence: 99%